1976
DOI: 10.1172/jci108375
|View full text |Cite
|
Sign up to set email alerts
|

Effect of protein ingestion on splanchnic and leg metabolism in normal man and in patients with diabetes mellitus.

Abstract: A B S T R A C T The inter-organ flux of substrates after a protein-rich meal was studied in seven healthy subjects and in eight patients with diabetes mellitus. Arterial concentrations as well as leg and splanchnic exchange of amino acids, carbohydate substrates, free fatty acids (FFA), and ketone bodies were examined in the basal state and for 3 h after the ingestion of lean beef (3 g/kg body wt). Insulin was withheld for 24 h before the study in the diabetic patients.In the normal subjects, after protein ing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
138
2
5

Year Published

1977
1977
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(161 citation statements)
references
References 45 publications
(60 reference statements)
14
138
2
5
Order By: Relevance
“…Previous studies have also demonstrated a consistently negative amino acid balance in traumatized and septic patients on intravenous nutrition (27), and in patients on enteral nutrition (2). It is, however, obvious that it is possible to obtain a net uptake of amino acids across skeletal muscle in normal individuals simply by increasing the infusion rate of amino acids, which leads to increased arterial levels (Table III [28,29]). …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have also demonstrated a consistently negative amino acid balance in traumatized and septic patients on intravenous nutrition (27), and in patients on enteral nutrition (2). It is, however, obvious that it is possible to obtain a net uptake of amino acids across skeletal muscle in normal individuals simply by increasing the infusion rate of amino acids, which leads to increased arterial levels (Table III [28,29]). …”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, its physiologic significance and role in diabetes mellitus has recently been questioned by observations that sustained hyperglucagonemia causes only a transient increase in glucose production in vivo (2)(3)(4)(5), and that prolonged exposure of the liver to hyperglucagonemia in vitro results in diminished ability of glucagon to stimulate glycogenolysis (6), to activate adenylate cyclase (7), and to bind to its plasma membrane receptors (8)(9)(10). However, because glucagon secretion varies throughout the day as a result of intermittent stimuli such as meals (11)(12)(13)(14), exercise (15,16), and stress (17,18), the liver in vivo is usually exposed to fluctuating glucagon levels; thus, conclusions based upon the effects of sustained hyperglucagonemia may not necessarily reflect the actions of glucagon under physiologic conditions. The present studies were, therefore, undertaken to examine the effects on glucose homeostasis of intermittent hyperglucagonemia produced endogenously by administration of the glucagon secretagogue arginine in normal and diabetic man.…”
Section: Introductionmentioning
confidence: 99%
“…Catheter sheaths were placed in the right femoral artery and femoral vein between 7 and 8 A.M. Hepatic vein catheters were inserted under fluoroscopic guidance, and appropriate positioning was confirmed by nonionic contrast injection (18). A femoral artery catheter was inserted through the arterial sheath.…”
mentioning
confidence: 99%
“…A slow infusion of normal saline was used to maintain patency of the catheters. The femoral artery sheath was used for infusion of indocyanine green to measure blood flow in the leg and splanchnic regions using indicator dye dilution techniques (18,19 …”
mentioning
confidence: 99%